2009
DOI: 10.1007/s10384-009-0657-8
|View full text |Cite|
|
Sign up to set email alerts
|

Axonal regeneration induced by repetitive electrical stimulation of crushed optic nerve in adult rats

Abstract: TES applied daily promotes both axonal regeneration and survival of RGCs after ON crush.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 31 publications
2
56
0
1
Order By: Relevance
“…Enhanced survival of RGCs has also been observed after optic nerve crush, 15,16,20,32 after light-induced retinal damage, 26 and in ischemic rat retinas. 33 Tagami et al 32 revealed that the increased survival of RGCs was in accordance with the number of TES applications and that the daily application of TES exhibited the most effect.…”
Section: Tes In Animal Modelsmentioning
confidence: 87%
See 3 more Smart Citations
“…Enhanced survival of RGCs has also been observed after optic nerve crush, 15,16,20,32 after light-induced retinal damage, 26 and in ischemic rat retinas. 33 Tagami et al 32 revealed that the increased survival of RGCs was in accordance with the number of TES applications and that the daily application of TES exhibited the most effect.…”
Section: Tes In Animal Modelsmentioning
confidence: 87%
“…33 Tagami et al 32 revealed that the increased survival of RGCs was in accordance with the number of TES applications and that the daily application of TES exhibited the most effect. Furthermore, daily TES administration resulted in the up-regulated expression of IGF-1 to a greater extent than a single application of TES.…”
Section: Tes In Animal Modelsmentioning
confidence: 94%
See 2 more Smart Citations
“…They have also collected evidence for enhanced survival of ganglion cells after optic nerve injury [9][10][11][12][13] (crush or axotomy), for increased survival of different retinal cell populations after light-induced retinal damage [14,15], and for increased cell survival in ischemic rat retinas [16]. Likely mechanisms, elucidated in these experiments, include advantageous regulation of neurotrophins such as endogenous insulin-like growth factor (IGF)-1 [10,14,17] and Fgf2 [18], involvement of B-cell lymphoma 2 (Bcl-2)…”
Section: Animal Experimentsmentioning
confidence: 99%